2011
DOI: 10.1016/j.vaccine.2011.09.069
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with drifted variants of avian H5 hemagglutinin protein elicits a broadened antibody response that is protective against challenge with homologous or drifted live H5 influenza virus

Abstract: Substantial H5 influenza HA directed immunity is elicited after vaccination of human subjects who had been previously immunized with a drifted H5 HA variant. We sought to investigate the characteristics of H5 HA specific immune responses in more depth by developing an animal model of H5 HA vaccination using drift variants of recombinant H5 HA proteins. HA proteins derived from influenzas A/Vietnam/1203/04 (Clade 1) and A/Indonesia/05/05 (Clade 2.1) were chosen. The sequence of vaccination consisted of two dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…An important and exciting finding is that mice vaccinated with HA plus 17-HDHA had minimal weight loss and complete survival as compared to vehicle and mock vaccinated control groups. Vaccinating mice with recombinant HA alone, even though it did not produce detectable neutralizing antibody levels, it did generate a protective immune response (80% survival rate), which has been previously reported (24). Notably, 17-HDHA vaccinated mice had a 100% survival rate.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…An important and exciting finding is that mice vaccinated with HA plus 17-HDHA had minimal weight loss and complete survival as compared to vehicle and mock vaccinated control groups. Vaccinating mice with recombinant HA alone, even though it did not produce detectable neutralizing antibody levels, it did generate a protective immune response (80% survival rate), which has been previously reported (24). Notably, 17-HDHA vaccinated mice had a 100% survival rate.…”
Section: Discussionsupporting
confidence: 73%
“…In the absence of adjuvants, recombinant HA induces a poor humoral response (24). Current seasonal influenza vaccines (IIV, LAIV or RIV) do not use adjuvants (4, 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other immunological mechanisms may also have contributed to the cross-clade protection against H5N2 virus. Studies have suggested that both cell-mediated immunity and non-neutralizing antibodies, such as antibodies with antibody-dependent cell-mediated cytotoxicity (ADCC) activity, contribute to cross-clade protection in the absence of a detectable neutralizing antibody response (Lipatov et al, 2006; Santiago et al, 2011). ADCC assays measure HA-binding, non-neutralizing antibodies and thus it is conceivable that non-neutralizing antibodies from vaccinated ferrets in our current study confer protection against H5N2 virus through the ADCC pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse monoclonal antibody against Viet HA (NR-2730) and goat polyclonal anti-X31 NR-3118 were obtained from BEI Resources (NIAID, NIH). Mouse polyclonal anti-Indo HA sera (3xIndo) was obtained from mice immunized three times, at two-weeks intervals, with 2 µg of recombinant Indo H5 (BEI Resources, NR-10511) adjuvanted with CpG oligonucleotides (ODN-1826), as previously described [37]. NAbs are summarized in Appendix 1 .…”
Section: Methodsmentioning
confidence: 99%